Psychosocial Experiences of Adolescent Girls and Young Women Subsequent to an Abortion in Sub-saharan Africa and Globally: A Systematic Review - Zia, Yasaman; Mugo, Nelly; Ngure, Kenneth; Odoyo, Josephine; Casmir, Edinah; Ayiera, Eric; Bukusi, Elizabeth; Heffron, Renee (Frontiers in Reproductive Health, 2021)
Introduction: Unmet need for contraception, unintended pregnancy, and access to safe abortion remain global challenges preventing adolescent girls and young women (AGYW) from achieving optimal reproductive health. Furthermore, AGYW face difficulties navigating sexual autonomy, lack of agency or experience negotiating sexual acts, and challenges accessing sexual health information and services. The aim of this systematic review is to assess the psychosocial outcomes of AGYW who have experienced an abortion with particular focus on sub-Saharan Africa, which bears the global burden of unintended pregnancy and risk of death due to unsafe abortion. Materials and Methods: The systematic review was registered and used search terms to identify peer-reviewed articles relevant to “post-abortion,” “psychosocial,” “adolescent girls,” and “young women” from PubMed, Embase, PsycInfo, and Cumulative Index to Nursing and Allied Health Literature. Examples of psychosocial experiences include quality of life, stigma, and mental health outcomes. Rayyan software (Qatar, 2020) was used by two reviewers to assess the relevance of each article to psychosocial outcomes of AGYW any time after an abortion or accessing post-abortion services. Analysis was conducted with a focus on data from Africa and comparisons are made to non-African settings. Results: A total of 2,406 articles were identified and 38 articles fit the criteria. Six selected articles were from Africa, including Ghana, Kenya, Uganda, and Zambia, and the remaining articles were from other regions. Themes around stigma, shame, and abandonment associated with the experience of abortion were prevalent in all regions. Studies of psychosocial outcomes of AGYW in sub-Saharan Africa highlight social isolation as well as learned resilience among young women who abort. Discussion: Navigating abortion as an AGYW involves managing internalized and perceived stigma, fear of violence, secrecy, and growing resilient in order to overcome the significant barriers that society and culture place on access to an essential service in sexual and reproductive health. Post-abortion psychosocial outcomes highlight the need for support services and investigation of contexts that perpetuate and necessitate unsafe abortion. Empowerment of AGYW may present an important opportunity to build self-agency and positive coping mechanisms to withstand social pressures during stigmatizing circumstances associated with abortion.